Med sinhronim in diahronim pogledom - Kavčič, Jerneja (Keria (Ljubljana), 2011)
The description of the syntax of the infinitive in Hellenistic and Byzantine Greek is dominated by the historical approach, which interprets syntactic changes in the light of the anticipated disappearance of the infinitive. However, the syntax of the infinitival clauses dating from these two periods displays phenomena apparently not known to Classical Greek, at least not in an identical form. Moreover, these phenomena cannot be adequately explained as signs heralding the disappearance of the infinitive. The paper addresses: (1) the use of the AcI structure when the subject of the main clause is coreferential with that of an indicative infinitival clause dependent on a verb of speaking or thinking; (2) the use of negative particles in infinitival clauses dependent on verbs of speaking or thinking; (3) the use of the infinitive in indirect questions. It is particularly the use of the infinitive in deliberative indirect questions of the 'I did not know what to do' type that argues against construing the syntax of Hellenistic and Byzantine Greek infinitival clauses as a mere trend towards the limitation and final disappearance of the infinitive. Arguably the clauses of this type originated as late as the Hellenistic period, while Jannaris' attempt to explain them as a wrong use of the infinitive, caused by its decline, is not convincing. Hellenistic Greek also witnessed a change in the use of negative particles in indicative infinitival clauses and in the use of the AcI structure where the subject of the main clause was coreferential with that of the infinitival clause. Especially texts written in the demotic language display a gradual predominance of the particle 'me' where Classical Greek would require 'ou(k)'. Where the subjects are coreferential, moreover, an alternative to an infinitival clause, with the subject left unexpressed, is the AcI structure (which, in contrast to Classical Greek, places no emphasis on the subject of the infinitival clause). While a connection between these two phenomena and the gradual disappearance of the infinitive cannot be ruled out, the two changes may well have evolved quite independently of the disappearing process.
Keywords: bizantinska grščina; Byzantine Greek; grščina; helenistična grščina; Hellenistic Greek; infinitive; nedoločnik; skladnja; syntax